Dye-sensitized solar cell using pure anatase TiO2 annealed at different temperatures - M. Fazli, F.I.; Ahmad, M.K.; Soon, C.F.; N., Nafarizal; Suriani, A.B.; Mohamed, A.; Mamat, M.H.; Malek, M.F.; Shimomura, M.; Murakamid, K. (Elsevier Science Ltd, 2017)
The performance of pure anatase titanium dioxide (TiO2) annealed at different tempera-tures as photoanode in the application of dye-sensitized solar cell (DSSC) was investigated and discussed. All samples of TiO2 were deposited on ﬂuorine-doped tin oxide (SnO2) on glass substrate using spray pyrolysis deposition (SPD) method. Characterizations of the DSSCs fabricated were executed on their surface morphology, structural property, and energy conversion efﬁciency. In the DSSC preparation, anatase TiO2 thin ﬁlms, platinum (Pt), ruthenium-based dye N719 and DPMII triiodide couple electrolyte were used as pho-toanodes, cathode/counter electrode, dye sensitizers and liquid electrolyte, respectively. All of the TiO2 photoanodes were annealed at 300 ◦C, 400 ◦C and 500 ◦C with a set left without any heat treatment. The thickness of anatase TiO2 photoanodes measured were in between 23 m and 41 m. The power conversion efﬁciency of DSSCs performed under visible light with intensity of 100 mW/cm2 shows that DSSC with pure anatase phased TiO2 annealed at 500 ◦C as photoanode yields the highest efﬁciency of 3.25%.